Researching terrorism, peace and conflict studies interaction, synthesis and opposition - Tellidis, Ioannis; Toros, Harmonie (Critical terrorism studies, 2015)
This book examines potential synergies between the fields of Terrorism Studies and Peace and Conflict Studies. The volume presents theoretically- and empirically-informed contributions, which shed light on whether the two fields can inform each other on issues of mutual interest and importance. The book examines key themes including the conceptualisation(s) of peace and violence; the exceptionalisation of terrorist violence; the relationship between scholarship and political power; the dysfunctionality of the liberal peace and the opportunities offered by post-liberal peacebuilding frameworks